Too much of a good thing: a case report detailing two instances of cerebral hyperperfusion syndrome. Issue 5 (8th May 2017) - Colibaba, Alexandru; Calma, Aicee; Zhai, Shaun; Gawarikar, Yash; Lueck, Christian
Abstract : Objectives: Cerebral hyperperfusion syndrome (CHS) is an uncommon but serious complication of carotid endarterectomy (CEA). Changes in mental status, headache, seizures and focal neurological deficits are common presenting symptoms 1 . The condition can occur up to 28 days after CEA. Impairment of cerebral vascular autoregulation has been implicated in the pathogenesis of the disease 2 . This study aims at presenting our experiences with CHS cases. Methods: We conducted a retrospective review of the admissions to the neurology ward at the Canberra hospital and Calvary hospital, Bruce, ACT in 2016 to identify patients diagnosed with CHS. Individual patient records were then examined for patients' demographics, symptomatology, examination findings, imaging findings and treatment outcomes. Results: Two patients were identified from the registry data. The first patient was an 80-year-old man who presented 10 days after a left-sided CEA with right hemiparesis, seizures, hypertension and confusion. There was a significant amount of T2 hyperintensity in the left hemisphere on the MRI of the brain. An MRI perfusion scan showed significantly increased cerebral blood flow in the left middle cerebral artery territory. Despite seizure treatment and supportive cares, the patient succumbed to his illness. The second patient was an 86-year-old woman who had bilateral carotid stenosis (80%–90% on the left and 50%–69% on the right). On day 6 post left-sided CEA, she was hospitalised for seizures. She was intubated briefly due to significant agitation and treated with antiepileptic medications. MRI showed similar hyperintense lesions on the left hemisphere. There was no restricted diffusion. She made an uneventful recovery and was discharged home. Conclusions: Our cases highlighted the significant morbidities and mortalities associated with CHS. Physician awareness can be important in the early recognition and treatment of this condition.